Purification of a recombinant glutathione transferase from the causative agent of hydatidosis, Echinococcus granulosus. Issue 1 (7th October 2015) - Fleitas, Andrea L.; Randall, Lía M.; Möller, Matías N.; Denicola, Ana
Abstract: This practical class activity was designed to introduce students to recombinant protein expression and purification. The principal goal is to shed light on basic aspects concerning recombinant protein production, in particular protein expression, chromatography methods for protein purification, and enzyme activity as a tool to evaluate purity and conformation of the recombinant product. Herein, we describe the purification of a glutathione transferase from the human parasite Echinococcus granulosus (EgGST1), the causative agent of hydatidosis. EgGST1 is expressed fused to a histidine tag and is purified by immobilized metal affinity chromatography. Protein quantification based on direct (UV absorbance) and indirect (colorimetric) methods are used and discussed. A simple colorimetric assay is used to measure GST activity and special emphasis is put on how to use these measurements to follow protein purification yields, its enrichment and its correct folding along the purification process. EgGST1 is easily expressed with high yields, purified in absence of protease inhibitors and proved to be robust concerning enzyme activity and protein integrity on a 1 week practical activity. © 2015 by The International Union of Biochemistry and Molecular Biology, 44:28–37, 2016.